1992
DOI: 10.1007/bf01046164
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical analysis of rat testicular glycoconjugates. 2. ?-galactosyl residues in O- and N-linked glycans in seminiferous tubules

Abstract: Rat testes have been examined with a panel of lectins that bind specifically to oligosaccharide sequences having terminal or subterminal beta-galactosyl residues in O-linked glycans, or in the outer chains of complex N-linked glycans: Arachis hypogaea (peanut, AHA), Erythrina cristagalli (coral tree, ECA), Ricinus communis (castor bean, RCA120) and Abrus precatorius (jequirity bean, APA) agglutinins. Pretreatment of sections with neuraminidase, beta-galactosidase and removal of alkali-labile O-linked sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…Although dramatic changes to carbohydrate structures during the development of testicular cells were suggested by histological analysis using a series of lectins (24), it is very difficult to determine the precise structure of such carbohydrates. In order to detect whether the GalNAc␤1-3GlcNAc structure exists or not, a tool is needed for probing such a structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although dramatic changes to carbohydrate structures during the development of testicular cells were suggested by histological analysis using a series of lectins (24), it is very difficult to determine the precise structure of such carbohydrates. In order to detect whether the GalNAc␤1-3GlcNAc structure exists or not, a tool is needed for probing such a structure.…”
Section: Discussionmentioning
confidence: 99%
“…Both O-and N-glycans can occur in the same glycoprotein. In the rat testis it has been demonstrated that both types of glycoconjugate are present (Martlnez-Menfirguez et al, 1993;Jones et al, 1993), but no information is available for the epididymis. Many methods have been employed to determine the type of glycoconjugate present; for example, use has been made of ]3-elimination (which cleaves the O-glycoconjugates) in combination with 0018-2214 9 1995 Chapman & Hall lectins.…”
Section: Introductionmentioning
confidence: 96%
“…Cells Tissues Organs 2007;185: [269][270][271][272][273][274][275][276][277][278][279][280][281][282][283][284] 271 SBA, SNA-1, MAA, PAA and WGA were also exposed to neuraminidase (0.1 units/ml, type VI from Clostridium perfringens , Sigma) [Jones et al, 1992] for 2 h at 37 ° C before incubation in the lectin to cleave off terminal sialic acid. Comments on the results of pretreatment with neuraminidase will be restricted to those which showed a clear effect.…”
Section: Glycosylation Of Hemomonochorial Placentaementioning
confidence: 99%